Optical and molecular indices of dissolved organic matter for estimating biodegradability and resulting carbon dioxide production in inland waters: A review. (1st January 2023) - Begum, Most Shirina; Park, Ji-Hyung; Yang, Liyang; Shin, Kyung Hoon; Hur, Jin
Highlights: BDOC measurement via DOC loss is the most accurate among available methods. DOM optical and molecular indices can act as surrogates for BDOC and dissolved CO2 . SUVA254, HIX, and terrestrial humic- and protein-like FDOM are recommended proxies. Potentials and limitations of previously proposed DOM indices are critically discussed. Abstract: Biodegradable dissolved organic carbon (BDOC) constitutes the most labile fraction of dissolved organic matter (DOM), which also functions as a source of CO2 emissions from inland waters. However, no systematic review is available on DOM indicators of BDOC and CO2 production potential. Optical and molecular indices can be used to track small changes in DOM composition during biodegradation. In this review, we identified four different methods for measuring BDOC together with their strengths and limitations. In addition, we discuss the potential of using documented optical indices based on absorption and fluorescence spectroscopy and molecular indices based on Fourier transform ion cyclotron mass spectrometry as proxies for estimating BDOC and biodegradation-induced CO2 production based on previously reported relationships in the literature. Many absorbance- and fluorescence-based indices showed inconsistent relationships with BDOC depending on watershed characteristics, hydrology, and anthropogenic impacts. Nevertheless, several indices, including specific UV absorbance at 254 nm (SUVA254 ), humification index (HIX), and terrestrial humic-like fluorescent DOM (FDOM) components, tended to have negative relationships with BDOC in tropical and temperate watersheds under baseflow or drought periods. Protein-like FDOM exhibited the strongest correlation with BDOC in different systems, except during storms and flood events. Despite the limited number of studies, DOM molecular indices exhibited consistent relationships with BDOC, suggesting that the relative abundance of aliphatic formulas and the molecular lability index could act as reliable proxies. The DOM optical indices explain up to 96% and 78% variability in BDOC and CO2, respectively; nonetheless, there were limited studies on molecular indices, which explain up to 74% variability in BDOC. Based on literature survey, we recommend several sensitive indices such as SUVA254, HIX, and terrestrial humic- and protein-like FDOM, which could be useful indicators of BDOC and dissolved CO2 in inland water. Future research should incorporate a wider range of geographic regions with various land use, hydrology, and anthropogenic disturbances to develop system- or condition-specific DOM optical or molecular proxies for better prediction of BDOC and CO2 emissions. Graphical abstract: Image, graphical abstract